2008
DOI: 10.1068/p5727
|View full text |Cite
|
Sign up to set email alerts
|

Independent Processing of Form, Colour, and Texture in Object Perception

Abstract: Most investigations of object recognition have focused on the form rather than the material properties of objects. Nevertheless, knowledge of the material properties of an object (via its surface cues) can provide important information about that object's identity. In this study, we used Garner's speeded-classification task to explore whether or not the processing of form and the processing of surface properties are independent. In experiment 1, participants made length and width classifications in an initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
68
5
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 56 publications
13
68
5
1
Order By: Relevance
“…If representations for different features of objects are sustained in independent, noisy neural populations but are assisted by a reactivation mechanism that acts in an object-based fashion, then this could produce object-based benefits without storage of object-based representations. On this view, features that are coded independently perceptually and neurally (so called separable dimensions, Cant et al, 2008;Drucker, Kerr, & Aguirre, 2009;Garner, 1974;Livingstone & Hubel, 1988), such as color and orientation may have largely independent instances of representational failure, whereas integral features such as height and width (Garner, 1974) may fail together.…”
Section: Resultsmentioning
confidence: 99%
“…If representations for different features of objects are sustained in independent, noisy neural populations but are assisted by a reactivation mechanism that acts in an object-based fashion, then this could produce object-based benefits without storage of object-based representations. On this view, features that are coded independently perceptually and neurally (so called separable dimensions, Cant et al, 2008;Drucker, Kerr, & Aguirre, 2009;Garner, 1974;Livingstone & Hubel, 1988), such as color and orientation may have largely independent instances of representational failure, whereas integral features such as height and width (Garner, 1974) may fail together.…”
Section: Resultsmentioning
confidence: 99%
“…The order of the blocks was counterbalanced across participants in each group (i.e., half of the participants were randomly allocated to start with the baseline blocks, and the other half started with the filtering blocks); each matched control performed the experiment in the same order as their respective CP. Previous studies using the Garner paradigm with similar stimuli have used a full design (i.e., judging width while height was irrelevant and vice versa) and reported symmetric effects (Cant, Large, McCall, & Goodale, 2008;Dykes, 1979).…”
Section: Methodsmentioning
confidence: 97%
“…Although the above mentioned fMRI evidence points to textures being processed in striate area V1 other studies have shown that a variety of extra-striate areas (e.g. V2, V4, TEO) are involved in processing different types of texture (Baker et al, 2006;Cant & Goodale, 2007;Cant et al, 2008;Freeman et al, 2013;Kastner, De Weerd, & Ungerleider, 2000).…”
Section: Experimental Evidence For De-texturizationmentioning
confidence: 95%